Decoupling the Effects of the Amyloid Precursor Protein From Amyloid-β Plaques on Axonal Transport Dynamics in the Living Brain - Medina, Christopher S.; Uselman, Taylor W.; Barto, Daniel R.; Cháves, Frances; Jacobs, Russell E.; Bearer, Elaine L. (Frontiers in Cellular Neuroscience, 2019)
Amyloid precursor protein (APP) is the precursor to Aβ plaques. The cytoplasmic domain of APP mediates attachment of vesicles to molecular motors for axonal transport. In APP-KO mice transport of Mn2+ is decreased. In old transgenic mice expressing mutated human (APPSwInd) linked to Familial Alzheimer’s Disease, with both expression of APPSwInd and plaques, the rate and destination of Mn2+ axonal transport is altered, as detected by time-lapse manganese-enhanced magnetic resonance imaging (MEMRI) of the brain in living mice. To determine the relative contribution of expression of APPSwInd versus plaque on transport dynamics, we developed a Tet-off system to decouple expression of APPSwInd from plaque, and then studied hippocampal to forebrain transport by MEMRI. Three groups of mice were compared to wild-type (WT): Mice with plaque and APPSwInd expression; mice with plaque but suppression of APPSwInd expression; and mice with APPSwInd suppressed from mating until two weeks before imaging. MR images were captured before at successive time points after stereotactic injection of Mn2+ (3-5nL) into CA3 of the hippocampus. Mice were returned to their home cage between imaging sessions so that transport would occur in the awake freely moving animal. Images of multiple mice from the three groups (suppressed or expressed) together with C57/b6J WT were aligned and processed with our automated computational pipeline, and voxel-wise statistical parametric mapping (SPM) performed. At the conclusion of MR imaging, brains were harvested for biochemistry or histopathology. Paired T-tests within-group between time points (p = 0.01 FDR corrected) support the impression that both plaque alone and APPSwInd expression alone alter transport rates and destination of Mn2+ accumulation. Expression of APPSwInd in the absence of plaque or detectable Aβ also resulted in transport defects as well as pathology of hippocampus and medial septum, suggesting two sources of pathology occur in familial Alzheimer's disease, from toxic mutant protein as well as plaque. Alternatively mice with plaque without APPSwInd expression resemble the human condition of sporadic Alzheimer's, and had better transport. Thus, these mice with APPSwInd expression suppressed after plaque formation will be most useful in preclinical trials.